2017
DOI: 10.5121/ams.2017.4301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and its Associated Factos in Adults with Diabetes Mellitus : A Cross - Sectional Study in a Teritary Care Centre

Abstract: (adjusted odds ratio=3.02, 95% CI: 1.17 to 7.7, P=0.022). Also, employed people were at a lower risk for depression when compared to the unemployed /retired population (adjusted odds ratio=0.319, P=0.023

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…7 Presence of hypertension: defined in the study as systolic BP level of ≥140 mmHg and diastolic BP of ≥90 mmHg, or current treatment for hypertension with prescription medication. 13,16 Data Collection Method and Quality Control…”
Section: Operational Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Presence of hypertension: defined in the study as systolic BP level of ≥140 mmHg and diastolic BP of ≥90 mmHg, or current treatment for hypertension with prescription medication. 13,16 Data Collection Method and Quality Control…”
Section: Operational Definitionmentioning
confidence: 99%
“…Similarly, having hypertension has been identified as a significant factor for depression in studies conducted in Pakistan 33 and India. 13 Moreover, a community-based cross-sectional study conducted in Duhabi-Bhaluwa, Nepal revealed that having an additional illness increases the likelihood of developing major depressive disorder among people with T2DM. 1 These findings reflect the fact that having hypertension is seen to be an obvious burden to the existing illness.…”
Section: Factors Significantly Associated With Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worthwhile to note that our study did not find any association between occupation and depression among the participants. However, a study in India revealed that depression among diabetic clients was significantly associated with some socio-demographic factors with a higher prevalence in the unemployed population [ 27 ]. The reasons for the lack of association between occupation status and depression among diabetics patients in the present study are not well understood.…”
Section: Discussionmentioning
confidence: 99%